(untitled) (Eurasian Journal of Ecology, 2022)
In our work, we conducted a number of scientific research works to create the bottom sediments of local reservoirs, rich in organic and mineral substances, for the needs of agriculture. The article provides information on the total volume of wastewater and the share of untreated wastewater over the last 10 years. By analyzing the condition of water reservoirs in the local area, a vermitechnology-based method of bottom sediment treatment was developed. Ways of using vermicompost fertilizer based on bottom sediments and humic acids based on it as a biostimulant for plants are shown. An inversion voltammetric laboratory analysis was carried out with the Ta-Lab apparatus for the determination of heavy metals (Pb, Zn) in the original sediments. After treatment with vermitechnology, the content of heavy metals in the samples of the bottom sediments of the reservoir was slightly reduced compared to the initial indicators, for example, in the substrate Koshkorgan Zn 11 mg/kg, Pb 0.92 mg/kg; and in the substrate Ermakozen Zn 4.1 mg/kg, Pb 5.1 mg/kg; in the substrate Shert Zn 21.9 mg/kg, Pb 0.6 mg/kg. The Orlov method was used to extract humic acids from vermicompost. The amount of organic matter and humic acids contained in biohumus can be compared in the following sequence: Koshkorgan > Shert > Ermakozen. Laboratory parameters obtained from the results of the study were determined on the basis of regulatory requirements and methods. Key words: reservoir; groundwater; bottom sediment; California red worms; vermitechnology; vermicompost; agriculture, soil.